Development of Acehnese Local Wisdom-Based Visual Art Worksheet to Enhance Early Childhood Creativity - Veryawan Veryawan; Rabitah Hanum Hasibuan; Arie Dwi Ningsih; Ade Tursina; Nur Balqis Mutia; Masganti Sit; Anita Yus; Yusnadi Yusnadi (Journal of Childhood Development, 2026)
This study aims to develop and empirically validate Acehnese local wisdom-based visual art worksheets to enhance creativity in children aged 4–6 years. Employing a Research and Development (R&D) approach with the ADDIE model, the research was conducted at Taman Indria Kindergarten, Langsa City, involving 30 children, four teachers, and three expert validators. Data were collected through observations, interviews, validation sheets, creativity assessment rubrics, and documentation. The developed worksheets integrate elements of Acehnese culture such as traditional attire, vernacular architecture, local motifs, and cultural symbols into visual arts activities that include drawing, coloring, stamping, mosaic making, storytelling, and singing. Expert validation yielded very good criteria, averaging 95.6% (media: 95%, content: 98%, language: 94%). Implementation demonstrated positive responses, with operational feasibility reaching 98.1% (Very Feasible). Children's creativity scores improved significantly from pretest (M=59.3) to posttest (M=83.1), t(29)=12.457, p<0.001, with a moderate N-Gain of 0.59. The findings indicate that culturally contextualized visual art worksheets are feasible, practical, and effective in enhancing children's creativity across fluency, flexibility, originality, and elaboration dimensions, while simultaneously fostering cultural awareness in early childhood education.